A comparative analysis of electronic resources access problems at two university libraries. Issue 4 (2nd October 2018) - Brett, Kelsey
Abstract: After three years of collecting electronic resources of troubleshooting tickets in Springhare's LibAnswers at University of Houston Libraries, the author conducted an analysis of over 300 tickets. The type of problem was identified for each ticket and then categorized into a functional area using an existing categorization schema developed at University of Maryland, College Park Libraries. This article discusses the author's analysis and findings of troubleshooting tickets at University of Houston Libraries and a comparison of e-resources access problems at University of Houston Libraries and University of Maryland, College Park Libraries.